The more grave delict of child pornography. A commentary on Art. 6 § 1 n. 2 of the 2010 Sacramentorum sanctitatis tutela - SKONIECZNY, PIOTR (Prawo Kanoniczne, 2017)
The Author comments on the constitutive elements (objective, subjective and legal) of the offence specified in Art. 6 § 1 n. 2 SST/2010. He calls for the extension of the term 'child pornography' to include the so-called pseudo child pornography according to international law. He criticises the wording of the norm (e.g. the 'turpe' element), and the limitation of child pornography to minors under the age of fourteen. He calls for a return to the punishment of child pornography on the basis of Art. 6 § 1 n. 1 SST/2010, changing the norm as follows: “delictum contra sextum Decalogi praeceptum cum minore vel in fraudem minoris infra aetatem duodeviginti annorum a clerico commissum”.